Cultivation of grey oyster mushroom [Pleurotus pulmonarius (Fr.) Quél.] on different alkaline materials and its antioxidant properties - Muhamad Pikri, Muhamad Fakhrul Radzi (2022)
The study aims to ascertain the effect of different alkaline materials’ supplementation on mushroom spawn, yield and antioxidant properties of grey oyster mushroom. The mushroom spawn grown on wheat with the treatment of zeolite (0.5%, 1%, 2%) and gypsum (1%, 2%) showed the rapid growth in spawnrunning time (10 days). The maize substrate coupled with all of the treatments and the wheat substrate with gypsum (1%, 2%) developed the thickest spawn mycelia. The antagonistic activity showed the wheat substrate with the treatment of zeolite (2%), and the maize substrate with zeolite (2%) exhibited a high growth inhibition rate against Trichoderma koningii with 91.67 ± 5.77 % and 90 ± 8.66 %, respectively. DNA analysis of mushroom pathogenic fungi proved the isolate of Trichoderma sp. was genetically similar with Trichoderma koningii at a bootstrap value of 97%. The cultivation of grey oyster mushrooms between different alkaline treatments was resolved to show the significant effect on mushroom production. The substrate in the presence of gypsum took minimum days for mycelial growth (30.7 ± 4.12 days) and the emergence of primordia (7.7 ± 4.55 days). The mushroom yield indicated that zeolite treatment showed the most significant yield (62.36 ± 9.67 g) as collected from the first until the fourth flush. The biological efficiency resembled by the treatment of zeolite stood out all the treatments by 26.05 ± 11.18 %. A maximum inhibitory effect against 2,2- diphenyl-1-picrylhydrazyl (DPPH) free radicals, IC50, was demonstrated by zeolite treatment at the third flush (63.48 ± 28.804 μg/mL). The fruiting body produced from the zeolite treatment was highly containing phenolic compound (98.96 ± 10.07 μg GAE/mg), as noticed in the fourth flush. Therefore, supplementation of gypsum and zeolite in substrate formulation might be a great benefit to practice in promoting and increasing the quality of spawn and fruiting body of mushrooms.